Examen especial a las cuentas Documentos y Cuentas por Cobrar de la Caja de Ahorro y Crédito del Sindicato Unido de Trabajadores de la EERSSA Primero de Abril del Cantón Loja, periodo 2022 - Zhanay Guachizaca, Rocio del Carmen (2024)
This Curricular Integration Work entitled “Special Examination of the accounts Documents and Accounts Receivable of the Savings and Credit Bank of the United Union of Workers of the EERSSA "Primero de Abril" of the Loja Canton, period 2022”, was developed in order to comply with the objectives that are aimed at the Evaluation of the Internal Control System, determine the reasonableness of the balances and the preparation of the final report containing comments, conclusions and recommendations which will collaborate with the improvement of the financial management of the Savings and Credit Bank. To begin the Special Examination of the accounts Documents and Accounts Receivable of the Savings and Credit Union of the United Union of Workers of the EERSSA "Primero de Abril" of the Loja Canton, period 2022, it starts with visits to the entity to apply methods such as observation and collection of information to verify the authenticity of the item to be examined. The corresponding phases were developed as Phase I which are the specific and preliminary where activities are carried out to plan and prepare the audit where they are carried out effectively and efficiently, Phase II was developed starting with the Audit Program and the Internal Control Questionnaire to analyze and evaluate the level of risk and confidence of the item Documents and Accounts Receivable, once performed it was shown that the savings and Loan, has a moderate level of risk and a moderate level of confidence with a percentage of 53.84%. Once the evaluation was concluded, the respective narrative reports of the findings were prepared, to determine the reasonableness of balances in each item, the respective narrative reports were prepared, as well as analytical reports were prepared for the subcomponents to comply with the procedures established in the audit program. The credit statement of eighteen members was requested, which was the number determined through the sampling process for the analysis of credit control, in the same way, a credit breakdown was obtained for the respective analysis of the follow-up of balance control, all this leads to the predetermination that there is a finding due to the lack of credit control, as well as the follow-up of balances in members.) Finally, the report of the Special Examination detailed in Phase III was drafted with their respective comments, conclusions and recommendations to be taken into account by the Legal Representative and the Accountant-Secretary to correct the exposed observations and the company takes care of its financial management.